Effects of B Chromosomes on Egg Fertility and Clutch Size in the Grasshopper Eyprepocnemis plorans - Bakkali, Mohammed; Manrique-Poyato, María Inmaculada; López-León, María Dolores; Perfetti-Álvarez, Francisco; Cabrero-Hurtado, Josefa; Martínez-Camacho, Juan Pedro (Pensoft, 2010)
We analyse here three components of reproductive success (egg fertility, egg clutch size and embryo clutch size) in several temporal samples from different Spanish and Moroccan populations of the grasshopper Eyprepocnemis plorans. The analysis of spatial and temporal variation suggests that egg clutch size, but neither embryo clutch size nor egg fertility depends significantly on both year of sampling and population of origin. While the former effect could mainly be due to year-to-year variation in food availability (essential to egg production but not to hatching success), the spatial variation may also include population-dependent genetic factors. We also tested the effect of the presence of supernumerary (B) chromosomes carried by many individuals in most natural populations of this species. We found a slight but significant decrease in egg fertility associated with the presence of B chromosomes. We discuss possible causes of the observed variation for these three reproductive traits at both spatial and temporal levels, as well as the effect of B-chromosome presence as a parasitic element disturbing reproduction of carrier females.
Keywords: Cromosomas; Cromosomas B; Tamaño de puesta; Fertilidad; Saltamontes; Ortópteros; Eyprepocnemis plorans